A catalog of CasX genome editing sites in common model organisms - Roberson, Elisha D. O. (BMC Genomics, 2019)
DpbCasX, also called Cas12e, is an RNA-guided DNA endonuclease isolated from Deltaproteobacteria. In this paper I characterized the CasX-compatible genome editing sites in the reference genomes of yeast (Saccharomyces cerevisiae), flatworms (Caenorhabditis elegans), flies (Drosophila melanogaster), zebrafish (Danio rerio), mouse (Mus musculus), rats (Rattus norvegicus), and humans (Homo sapiens). Across those genomes there were > 27,000 CasX sites per megabase on average. More than 90% of genes in each genome had at least one unique site overlapping an exon, with median unique sites per gene of 6–45. I also annotated sites in the GRCm38 reference and 15 additional mouse strain genomes. The presence of specific guide sequences varied amongst the strains, with CAST/EiJ and PWK/PhJ showing the greatest divergence from the reference strain. The high density of CasX sites and number of exon overlapping sites suggests that CasX has the potential to be used as a common genome editor. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5924-6) contains supplementary material, which is available to authorized users.